Investigation into the effect of deltoid ligament injury on rotational ankle instability using a three-dimensional ankle finite element model - Li, Yuandong; Tong, Jiahui; Wang, Huizhi; Ji, Xiaoxi; Hua, Yinghui; Cheng, Cheng-Kung (Frontiers in Bioengineering and Biotechnology, 2024)
Background Injury to the lateral collateral ligament of the ankle may cause ankle instability and, when combined with deltoid ligament (DL) injury, may lead to a more complex situation known as rotational ankle instability (RAI). It is unclear how DL rupture interferes with the mechanical function of an ankle joint with RAI. Purpose To study the influence of DL injury on the biomechanical function of the ankle joint. Methods A comprehensive finite element model of an ankle joint, incorporating detailed ligaments, was developed from MRI scans of an adult female. A range of ligament injury scenarios were simulated in the ankle joint model, which was then subjected to a static standing load of 300 N and a 1.5 Nm internal and external rotation torque. The analysis focused on comparing the distribution and peak values of von Mises stress in the articular cartilages of both the tibia and talus and measuring the talus rotation angle and contact area of the talocrural joint. Results The dimensions and location of insertion points of ligaments in the finite element ankle model were adopted from previous anatomical research and dissection studies. The anterior drawer distance in the finite element model was within 6.5% of the anatomical range, and the talus tilt angle was within 3% of anatomical results. During static standing, a combined rupture of the anterior talofibular ligament (ATFL) and anterior tibiotalar ligament (ATTL) generates new stress concentrations on the talus cartilage, which markedly increases the joint contact area and stress on the cartilage. During static standing with external rotation, the anterior talofibular ligament and anterior tibiotalar ligament ruptured the ankle’s rotational angle by 21.8% compared to an intact joint. In contrast, static standing with internal rotation led to a similar increase in stress and a nearly 2.5 times increase in the talus rotational angle. Conclusion Injury to the DL altered the stress distribution in the tibiotalar joint and increased the talus rotation angle when subjected to a rotational torque, which may increase the risk of RAI. When treating RAI, it is essential to address not only multi-band DL injuries but also single-band deep DL injuries, especially those affecting the ATTL.